ECM algorithms that converge at the rate of EM - Sexton, J; Swensen, AR (Biometrika, 2000)
We show that the ECM algorithm can always be constructed to converge at the same or approximately the same rate as the EM algorithm. The construction is based on the well-known conjugate directions algorithm. This result both suggests ways of speeding up the convergence of ECM and provides a simple way of identifying cases where the simplicity and stability of ECM over EM is attained at effectively no loss in convergence speed. Three examples are given.